Approach to development of mentoring potential in technical universities through the example of the Ural region of the Russian Federation - Guryanova, Inna; Burilkina, Svetlana; Martynova, Natalya; Kaminsky, Alexander; Mameteva, Olga (Journal of Applied Engineering Science, 2018)
New Federal State Higher Educational Standard introduces significant changes in the sense of purpose of education and overburdens professional adaptation of a starting teacher. In this regard, introduction of effective methods for developing a mentoring mechanism in the higher education system is updated. The goal of the research was to develop an approach to the definition and development of the mentoring potential in higher education institutions through the example of the Ural Region of the Russian Federation. Interviewing helped to analyze the need for mentorship and the level of its potential in universities of the Ural Region. A system of criteria for assessing the potential of a mentor in higher school was substantiated and structured. Using Harrington’s scale, qualitative levels of the potential of a young professional’s mentor in higher education institutions were determined based on quantitative scores. A mentor identification model was proposed, taking into account qualitative and quantitative criteria of the mentoring potential. A system of optimization measures for developing the mentoring mechanism in the higher education system of the Ural Region was substantiated. Practical implementation of the findings would facilitate effective adaptation of young professionals to teaching activities and develop their pedagogical potential.